Comparing the performance of conventional PCR, RTQ-PCR, and droplet digital PCR assays in detection of Shigella. (June 2020) - Yang, Jin; Zhang, Nana; Lv, Jun; Zhu, Ping; Pan, Xing; Hu, Jiaqingzi; Wu, Wenfeng; Li, Shan; Li, Hongtao
Abstract: The incidence of foodborne infections caused by Shigella spp. is still very high in every year, which poses a great potential threat to public health. Conventional quantification methods based on culture techniques, biochemical, and serological identification are time-consuming and labor-intensive. To develop a more rapid and efficient detection method of Shigella spp., we compared the sensitivity and specificity of three different polymerase chain reaction (PCR) methods, including conventional PCR, quantitative real-time PCR (RTQ-PCR), and droplet digital PCR (ddPCR). Our results indicated that ddPCR method exhibited higher sensitivity, and the limit of detection was 10 −5 ng/μl for genomic DNA templates, 10 −1 cfu/ml for Shigella bacteria culture. In addition, we found that ddPCR was a time-saving method, which required a shorter pre-culturing time. Collectively, ddPCR assay was a reliable method for rapid and effective detection of Shigella spp. Highlights: The ddPCR method showed a high specificity for the detection of Shigella spp. The detection limit of ddPCR in detecting Shigella is 10-fold sensitive than RTQ-PCR and 100-fold than conventional PCR. ddPCR shortened detection time by 4hrs and 2hrs compared to RTQ-PCR and conventional PCR in contaminated faeces. The ddPCR assay is more reliable and effective for detecting shigella spp., which could cause the inflammatory response.